Correction: Visualising mouse neuroanatomy and function by metal distribution using laser ablation-inductively coupled plasma-mass spectrometry imaging. Issue 10 (7th September 2016) - Paul, Bence; Hare, Dominic J.; Bishop, David P.; Paton, Chad; Nguyen, Van Tran; Cole, Nerida; Niedwiecki, Megan M.; Andreozzi, Erica; Vais, Angela; Billings, Jessica L.; Bray, Lisa; Bush, Ashley I.; et al.
Abstract : Correction for 'Visualising mouse neuroanatomy and function by metal distribution using laser ablation-inductively coupled plasma-mass spectrometry imaging' by Bence Paul et al., Chem. Sci., 2015, 6, 5383–5393.